Acceleration of fibroblast number and FGF-2 expression using Channa striata extract induction during wound healing process: in vivo studies in wistar rats - Gunawan Oentaryo; Istiati Istiati; Pratiwi Soesilawati (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2016)
Background: Wound healing is a biological process associated with tissue growth and regeneration. Wound healing process, is important to repair damaged tissue. Wound healing process consists of coagulation and hemostasis, inflammation, proliferation, as well as remodeling phases. The process can be accelerated by taking synthetic or non synthetic drugs. One of them is Channa striata extract. The extract contains albumin, copper, and zinc, which can be assumed to increase inflammatory cell infiltration, fibroblast proliferation, and collagen secretion. Purpose: This study aimed to reveal the effects of Channa striata extracts on fibroblast number and FGF-2 expression in mucosal wound healing process of the Wistar rats’ lower lip. Method: This research was a true laboratory experimental research with randomized post test only control group design. Samples of experiment were devided to experiment and control group that consist five samples each. Experimental group was treted with Channa striata extract and ethanol at concentration of 25%, 50%, and 100%. The fibroblast number and FGF-2 expresion were examined. Result: The number of fibroblasts in the treatment groups receiving Channa striata extract at concentrations of 25%, 50%, and 100% was higher than in the control group. The highest number of fibroblasts was found on day 3 at the concentration of 100% (p<0.05). Similarly, FGF-2 expression in the treatment groups receiving Channa striata at concentrations of 25%, 50%, and 100% was higher than in the control group. The highest expression of FGF-2 was found on day 3 at the concentration of 50% (p<0.05). Conclusion: Channa striata extract increased fibroblast number and FGF-2 expression in mucosa wound healing process.